Improving 5G wireless networks through OFDM integration with convolutional coding and pulse shaping - Prayoga, Kadek Agus Mahabojana Dwi; Nugraha, Made Dika; Prabawa, Nyoman Angga; Antara, I Nengah Ludra (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
The telecommunications industry has evolved significantly, with advancements from 1G to 4G and now towards 5G, promising enhanced data speeds and connectivity. Orthogonal Frequency Division Multiplexing (OFDM) is crucial in this transition due to its efficient spectrum utilization and ability to handle frequency-selective fading. However, OFDM is susceptible to Carrier Frequency Offset (CFO), leading to Inter-Carrier Interference (ICI) and degraded performance. This research investigates the impact of CFO on conventional OFDM systems and proposes mitigation techniques using Improved Sinc-power (ISP) pulse shaping and Convolutional Channel Coding. MATLAB simulations were conducted to analyze CFO-induced ICI in a standard OFDM system, followed by performance comparison with ISP-OFDM and ISP-OFDM combined with Convolutional Coding. The results demonstrate that CFO significantly increases ICI, causing a higher Bit Error Rate (BER). The application of ISP pulse shaping reduces the side-lobe interference of each subcarrier, while the combination of ISP pulse shaping and Convolutional Coding provides the best performance improvement, achieving a BER of approximately 0.0018. Overall, the integration of ISP and Convolutional Coding effectively mitigates CFO-induced degradation, offering a robust and reliable solution for future 5G wireless communication systems